A Review on Synthesis of Methane as a Pathway for Renewable Energy Storage With a Focus on Solid Oxide Electrolytic Cell-Based Processes - Biswas, Saheli; Kulkarni, Aniruddha P.; Giddey, Sarbjit; Bhattacharya, Sankar (Frontiers in Energy Research, 2020)
Environmental issues related to global warming are constantly pushing the fossil fuel-based energy sector toward an efficient and economically viable utilization of renewable energy. However, challenges related to renewable energy call for alternative routes of its conversion to fuels and chemicals by an emerging Power-to-X approach. Methane is one such high-valued fuel that can be produced through renewables-powered electrolytic routes. Such routes employ alkaline electrolyzers, proton exchange membrane electrolyzers, and solid oxide electrolyzers, commonly known as solid oxide electrolysis cells (SOECs). SOECs have the potential to utilize the waste heat generated from exothermic methanation reactions to reduce the expensive electrical energy input required for electrolysis. A further advantage of an SOEC lies in its capacity to co-electrolyze both steam and carbon dioxide as opposed to only water, and this inherent capability of an SOEC can be harnessed for in situ synthesis of methane within a single reactor. However, the concept of in situ methanation in SOECs is still at a nascent stage and requires significant advancements in SOEC materials, particularly in developing a cathode electrocatalyst that demonstrates activity toward both steam electrolysis and methanation reactions. Equally important is the appropriate reactor design along with optimization of cell operating conditions (temperature, pressure, and applied potential). This review elucidates those developments along with research and development opportunities in this space. Also presented here is an efficiency comparison of different routes of synthetic methane production using SOECs in various modes, that is, as a source of hydrogen, syngas, and hydrogen/carbon dioxide mixture, and for in situ methane synthesis.